Municipal panel data analysis for solid waste, local governments and citizen participation - P. Hernández Medina; D. Pinilla Rodríguez (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Solid waste management in Ecuador is the responsibility of the municipal autonomous decentralised governments and is structured in a value chain from waste collection to final disposal. This study aims to assess the impact of municipal governance, public engagement, and the presence of regulations on the quantity of solid waste collected and the probability of service delivery within the value chain. The existing body of research concerning solid waste management at the municipal level in Ecuador is relatively sparse, particularly in terms of longitudinal studies. This gap highlights the need for further investigation, as the current limitations in data hinder a comprehensive understanding of the subject.METHODS: The estimation of the relationships was developed through panel data models, focusing on both the volume of collections and probability of providing recovery, storage, transfer and disposal services. The explanatory variables are quality of the territorial development and land use plan goals, targets and indicators. Furthermore, these factors involve the execution of the investment plan budget financial sustainability, efficiency of expenditure, fiscal dependence, participation system, participation mechanisms, participatory budget, control mechanisms, public accountability, ordinance, municipal agency and gross value added. The current study investigates solid waste collection and the delivery of services in the value chain as the dependent variables, analyzing data from 221 municipalities in Ecuador during the timeframe of 2017 to 2022.FINDINGS: The findings indicate that in smaller municipalities, citizen participation – either through participatory budgeting or control mechanisms – influences solid waste collection. In the realm of financial management, the significance of fiscal dependency and financial sustainability is prominent; however, the aspect of planning typically does not exhibit a considerable impact. The chances of offering services such as storage, transfers, and utilization, characterized by limited regulatory oversight, are shaped by fiscal reliance and the existence of relevant ordinances, with no observable effect from citizen participation.CONCLUSION: The outcomes related to citizen participation and waste management are generally more favorable in smaller municipalities. This phenomenon can be linked to their enhanced social cohesion and less complex administrative systems, which promote the successful implementation of policies and initiatives that cater to the unique needs of the community. On the other hand, larger municipalities face greater challenges, such as bureaucracy and complexity in service coordination, which limits the impact of citizen participation. To increase the efficiency of solid waste management services in municipalities, irrespective of their size, it is crucial to innovate in fiscal management and to adopt clear regulatory frameworks.